Identifikasi Perbedaan Kinerja Keuangan Antara Bank Devisa Dengan Bank Non Devisa Di Indonesiaperiode 2013-2015 - Suciani, Amelia, Dra. Walfiatun Mukharomah,MM (2016)
This study aims to identify the identification of differences between the financial performance of foreign banks with non-foreign exchange bank in Indonesia period 2013-2015. This research is a descriptive research. The population in this study are all banking companies listed in Bank Indonesia during the period 2013-2015. The sample in the study was 30 (foreign banks) and 30 (non-bank foreign exchange). The sampling technique is purposive sampling data analysis technique used is by using descriptive analysis techniques and t-test. The results showed no significant differences between (CAR) Foreign Exchange Banks and Non-Bank Foreign Exchange with sig (0.515)> 0.05 is not a significant difference between (ROA) Foreign Exchange Banks and Non-Bank Foreign Exchange with sig (0.076)> 0 05. there is no significant difference between (LDR) Foreign Exchange Banks and Non-Bank Foreign Exchange with sig (0,622)> 0.05. there is no significant difference between (NPL) Foreign Exchange Banks and Non-Bank Foreign Exchange indicated by the value sig (0.852)> 0.05. there is no significant difference between (ROA) Foreign Exchange Banks and Non-Bank Foreign Exchange with sig (0,075)> 0.05. there is no significant difference between (NIM) Foreign Exchange Banks and Non-Bank Foreign Exchange with sig (0,075)> 0.05. Conclusion there is no difference between the financial performance of foreign banks with non-foreign exchange bank in Indonesiaperiode 2013-2015. Keywords: CAR, ROA, LDR, NPL, ROA, NIM, Foreign Exchange, Non-Exchange